HUKUM DAN KEKUASAAN - Anggraini, Jum (E-Journal Widya Yustisia, 2005)
Law an power can not be separated from one another. It is like the two sides of a coin. Law and power is inseparable because power is absolute without control of law. However, law without power will remain merely as written stipulation. Thus, if law is to be effective and implemented well, then power can force and pressure people to abide to the law